2023
DOI: 10.47191/ijcsrr/v6-i11-43
|View full text |Cite
|
Sign up to set email alerts
|

Use of Chicken Eggshell Powder to Improve Calcium Content in Egg-Milk Pudding as a Food to Prevent Stunting and its Sensory Acceptability

Suci Pebrianti,
Yusrima Syamsina Wardani,
Mufti Ghaffar
et al.

Abstract: Use of Chicken Eggshell Powder to Improve Calcium Content in Egg-Milk Pudding as a Food to Prevent Stunting and its Sensory Acceptability

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
1
0
8

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(11 citation statements)
references
References 16 publications
2
1
0
8
Order By: Relevance
“…Which was 1.6%. These results were in accordance with research by (Pebrianti et al .,2023) who found that the ash percentage of eggshell powder was 83.08%, which signified the availability of minerals in it. More than 95% of the mineral composition in eggshell powder was calcium in the form of calcium carbonate (CaCO3) and calcium phosphate (Ca (PO4)2).…”
Section: Proximate Analysis Of Eggshell Powdersupporting
confidence: 92%
See 2 more Smart Citations
“…Which was 1.6%. These results were in accordance with research by (Pebrianti et al .,2023) who found that the ash percentage of eggshell powder was 83.08%, which signified the availability of minerals in it. More than 95% of the mineral composition in eggshell powder was calcium in the form of calcium carbonate (CaCO3) and calcium phosphate (Ca (PO4)2).…”
Section: Proximate Analysis Of Eggshell Powdersupporting
confidence: 92%
“…The results suggest that (sample 5 %) has a higher acceptable value than the other treatments. These findings were congruent with the findings of (Pebrianti et al, 2023) who discovered that the organoleptic color quality of cookies is important. Because the addition of eggshell powder had no noticeable impact on the panelists' color choice, there was no variance in their level of preference for pudding color.…”
Section: Sensory Evaluation Of Cookies Samplessupporting
confidence: 89%
See 1 more Smart Citation
“…Dampak buruk dari limbah cangkang telur juga dapat mengenai hewan, tumbuhan, dan lingkungan yang berasal dari sifat abrasive, bau dan polusi udara serta penyebaran patogen yang ditimbulkan limbah cangkang telur (Saratale et al, 2021;Waheed et al, 2020) Cangkang telur terdiri dari bahan kering (98%) dan air (2%). Sebagian besar bahan kering dari cangkang telur berasal dari abu, yaitu sebanyak 79-93% dan protein sebanyak 3-5% (Pebrianti et al, 2023;Wijinindyah et al, 2023). Mineral utama yang mendominasi adalah kalsium yang berada dalam bentuk CaCO3, yaitu sebanyak 85-95%, beberapa trace elements seperti Zn, P, Fe, Mg, Zn, dan Cu (Luo et al, 2020;Ray et al, 2017;Wijinindyah et al, 2023).…”
Section: Pendahuluanunclassified
“…Pemanfaatan cangkang telur sebagai sumber kalsium dilakukan dengan terlebih dahulu diolah menjadi bentuk bubuk melalui proses perendaman, perebusan, dan pengeringan. Fortifikasi bubuk cangkang telur telah dilakukan pada berbagai produk pangan yang ditujukan untuk meningkatkan kandungan kalsium, diantaranya adalah permen jeli susu kedelai (Novelina et al, 2020), puding (Pebrianti et al, 2023), snack bar (Handayani et al, 2022), tekwan (Telisa et al, 2022), nuget ayam (Merta et al, 2020), jeli (Younas et al, 2021), muffins (Afzal, 2020), gingerbread (Arnold et al, 2022), biskuit (Shahnila et al, 2022), dan es krim (Hasan et al, 2023). Hasil penelitian tersebut menunjukkan bahwa penambahan bubuk cangkang telur secara signifikan dapat meningkatkan kandungan kalsium dibandingkan kontrol sehingga dapat disimpulkan bahwa bubuk cangkang telur memiliki potensi kesehatan dan layak dipertimbangkan untuk dapat ditambahkan pada pengolahan pangan.…”
Section: Pendahuluanunclassified